2014
DOI: 10.1631/jzus.a1400055
|View full text |Cite|
|
Sign up to set email alerts
|

Mass transfer and reaction kinetics of sulfuryl fluoride absorption with aqueous sodium hydroxide solutions

Abstract: Abstract:The mass transfer and reaction kinetics of sulfuryl fluoride (SO 2 F 2 ) absorption with aqueous sodium hydroxide (NaOH) solutions were studied in an experimental double-stirred cell. Results showed that SO 2 F 2 absorption with NaOH was followed by a reaction model employing a fast pseudo-first-order. The second-order rate constant for SO 2 F 2 absorption with aqueous NaOH solutions was determined to be 1.44 m 3 /(mol·s) at 298 K. Three models were used in this chemical absorption process, and in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Ravindar et al 10 studied application of sulfuryl fluoride in chemical transformations, and they pointed out chemical transformations using the readily available feedstock sulfuryl fluoride. Nie et al 11 studied mass transfer and the reaction kinetics of sulfuryl fluoride absorption with aqueous sodium hydroxide solutions. The results showed that the second-order reaction rate constant at 298 K is 1.44 m 3 (mol/s), and the enhancement factor model E = 68.08 mol/L was established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ravindar et al 10 studied application of sulfuryl fluoride in chemical transformations, and they pointed out chemical transformations using the readily available feedstock sulfuryl fluoride. Nie et al 11 studied mass transfer and the reaction kinetics of sulfuryl fluoride absorption with aqueous sodium hydroxide solutions. The results showed that the second-order reaction rate constant at 298 K is 1.44 m 3 (mol/s), and the enhancement factor model E = 68.08 mol/L was established.…”
Section: Introductionmentioning
confidence: 99%
“…studied application of sulfuryl fluoride in chemical transformations, and they pointed out chemical transformations using the readily available feedstock sulfuryl fluoride. Nie et al 11 . studied mass transfer and the reaction kinetics of sulfuryl fluoride absorption with aqueous sodium hydroxide solutions.…”
Section: Introductionmentioning
confidence: 99%